A Highly Efficient Plasmonic Polarization Conversion Metasurface Supporting a Large Angle of Incidence - Bo Cheng; Zengxuan Jiang; Yuxiao Zou; Guofeng Song (Crystals, 2024)
The angle of incidence of the compact polarization conversion device is crucial for practical use in integrated miniaturized optical systems. However, this index is often ignored in the design of quarter-wave plate based on metasurface. Herein, it is shown that a thick metallic cross-shaped hole array supports extraordinary optical transmission peaks controlled by a Fabry–Pérot (FP) resonator mode. The positions of these peaks have been proven to be independent over a large range of incidence angles. We numerically design a miniatured quarter-wave plate (QWP) with an 80 nm bandwidth (840~920 nm) and approximately 80% average efficiency capable of effectively functioning as a linear-to-circular (LTC) polarization converter at an incidence inclination angle of less than 30°. This angle-insensitive compact polarization conversion device may be significant in a new generation of integrated metasurface-based photonics devices.